The Influence of Consistency and Originality on Brand Loyalty Mediated by Brand Attachment among Fajar Batik Ponorogo Customers - Vellia Ekaprasti; Fery Setiawan; Titi Rapini (Manunggal Halim Jaya, 2027)
This study aims to analyze the influence of Consistency and Originality on Brand Loyalty, with Brand Attachment serving as a mediating variable among customers of Fajar Batik Ponorogo. The study employed a quantitative approach using primary data collected through questionnaires distributed to 158 respondents. The analysis was conducted using the Partial Least Squares (PLS) method with the assistance of SmartPLS 3.0 statistical software. The results indicate that Consistency and Originality have a positive and significant effect on both Brand Attachment and Brand Loyalty. In addition, Brand Attachment has a significant effect on Brand Loyalty and is able to mediate the relationship between Consistency and Originality and Brand Loyalty. Originality was found to be the variable with the strongest influence on Brand Attachment, while Consistency emerged as the dominant factor in shaping Brand Loyalty. The high R-Square values for Brand Attachment (75.3%) and Brand Loyalty (80.0%) indicate that the model has strong explanatory power. The findings of this study suggest that customer loyalty is influenced not only by product consistency and uniqueness but also by customers’ emotional attachment to the brand.